PEMBERDAYAAN USAHA JAMU JAHE INSTAN DI KOTA SURAKARTA DAN KABUPATEN SUKOHARJO MELALUI TEKNOLOGI PENGOLAHAN JAHE - Muttaqin, Hermansyah; Cahyadin, Malik; Widiyanti, Emi (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
This activity aims to increase ginger herbal medicine business in Surakarta and Sukoharjo through: improvement of the quality and quantity of production, improvement of business management, and improvement of business financial bookkeeping. Partners of this activity are SMEs of herbal ginger "Mahkota" and "Wahyu". Methods of implementation activities include business training and mentoring. Activity period is the first half of 2015. Based on these activities can be concluded that: (1) the business of herbal ginger instant "Mahkota" and "Wahyu" have received and used production mechines that has been provided by the team to improve the quantity and quality of instant ginger herbal products; (2) the businessmen of ginger herbal instant "Mahkota" and "Wahyu" have got the knowledge about the importance of product packaging to attract customers and maintain the quality of products; and (3) the businessmen of herbal ginger instant "Mahkota" and "Wahyu" have got the knowledge of recording financial transactions in a simple business bookkeeping and understand its benefits